WAYS OF ERROR CORRECTION IN ENGLISH LESSONS - Salomova , Malika Zohirovna (Innovative Development in Educational Activities, 2023)
Over the course of the past few decades, a lot of attention has been paid to error correction and the significance of it in the classroom of foreign languages. Correcting students’ mistakes is important, according to Corder (1967), in three different ways: First, they tell the teacher about the student’s progress and what still needs to be learned. Second, they provide evidence of how a language is learned and the learning strategies employed by the student. Thirdly, because making mistakes is seen as a tool used by learners to learn, they are essential to the learning process. The purpose of this paper is to highlight fundamental Error Analysis background research. It also tries to educate EFL teachers and educators about the most common mistakes made by EFL students and encourages language practitioners to think about important questions about the significance of error correction in the process of learning a second language, such as: how much correction should be given, when the mistake should be made, and how to correct the student without making them less motivated.